The Effect Of Green Organizational Culture And Green Reward On Organizational Citizenship Behavior With Organizational Commitment As Intervening Variables - Norma Sari Putri, Audi; Mustafa E. Q, Zainal (Devotion : Journal of Research and Community Service, 2022)
Green Human Resources Management (GHRM), known as "environmental" human resource management, is considered an essential tool for the successful implications of organizational sustainable development strategies. The purpose of this study were to analyze first the effect of green organizational culture and green rewards on organizational commitment. The second is to analyze the effect of organizational commitment and green organizational culture on organizational citizenship behavior. The third is to analyze the effect of green organizational culture and green rewards on organizational citizenship behavior through organizational commitment. This research are a quantitative research that  used 105 employees, who were determined by using the purposive sampling method as the sample. Data was obtained through the distribution of questionnaires. The analytical tool used in this study uses IBM SPSS software 21. The results show that green organizational culture and green reward have a positive effect on an organizational commitment. Organizational commitment has a positive effect on organizational citizenship behavior, the higher the organizational commitment, the higher the organizational citizenship behavior. The results of further hypothesis testing showed that green organizational culture and green rewards have a positive effect on organizational citizenship behavior through organizational commitment.